Management In Prospering The Mosque Case Study At Alfurqon Mosque Karangjati Kemranjen Banyumas Central Java - Sumin Abdussalam (Prosiding University Research Colloquium, 2021)
Mosques are the best places on earth. The mosque where the servants prostrate to AllahSWT. They pray, dhikr and do other worship.Good management is needed to carry out its functions properly. There are three mainpillars in the management needed to prosper a mosque. They are making the mosque acenter for Islamic and community activities; place of education and study, communityinformation center; and the place of collection and distribution of zakat, infaq, andshadaqoh. In addition to management, no less important is human resources (HR). Thuswe need cadres, cadres are the main assets that must be considered because they are theones who will continue the Islamic struggle in the future. Al Furqon Mosque KarangjatiKemranjen Banyumas since the change of the mosque administrator in 2016 has begun tomake improvements by learning to improve the management of how to prosper mosque,starting from mapping the area, collecting data on congregations, then making innovativeprograms. The service program as one of the programs at the Al Furqon KarangjatiMosque, Kemranjen Banyumas is the Fajr Bank program, that is collecting infaq at thetime of Fajr prayer then allocate the infaq as soft loans ( primarily for them who are Fajrcongregation), financial support for when they are sick, providing free ambulance servicesand then financing and arranging the funeral and burial for the deceased concregations ortheir relatives.With service improvement and good quality programs, the number of congregationspraying five times a day and assemblies ta'lim increases.